Not by word of mouth alone - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Even in cultures dominated by oral tradition and history, the promotion of readership and of the book is one of the surest ways of breaking the cycles of lean lives. The book records, informs, exhilarates, liberates and makes history. Plough some...